A Group Key Distribution Scheme for Wireless Sensor Networks in the Internet of Things Scenario. (6th December 2012) - Yu, Hong; He, Jingsha; Zhang, Ting; Xiao, Peng
Abstract : As an indispensable part of the Internet of Things (IoT), wireless sensor networks (WSNs) need to be completely integrated into the Internet. When an Internet user communicates with multiple sensor nodes in WSNs, secure group key management becomes necessary. However, most current group key management schemes developed for WSNs do not consider the Internet scenario while traditional group key management in the Internet is deemed to be not suitable for WSNs due to the resource constraint characteristics of WSNs. In this paper, we propose a group key distribution scheme for WSNs in the IoT scenario in which we organize sensor nodes into groups in a hierarchical structure. In the upper wired layer, an end-to-end secure communication protocol is used to distribute group keys for subgroups to the trusted head nodes and the head nodes then distribute the group keys through underlying tree-based topology and wireless multicast to minimize energy consumption. We also perform some quantitative analyses as well as experiments to show that our proposed scheme is secure and has t -revocation capability. The total cost of distributing and rekeying the group keys is also analyzed and compared to that in some other comparable schemes.